Antibacterial and antioxidant activity of Endophytic Fungal Extract Isolated from the Root of Sonneratia caseolaris - Noviyanto, Noviyanto; Oktiansyah, Rian; Nasution, Sakinah Salman Ahmad; Utami, Riza; Amelia, Dea (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2025)
Sonneratia caseolaris is a mangrove species of considerable pharmacological importance; however, its natural populations are increasingly threatened by habitat degradation and overexploitation. Endophytic biotechnology provides a sustainable alternative for exploring the bioactive potential of this plant without imposing additional pressure on its fragile ecosystem. This study aimed to evaluate the antibacterial and antioxidant activities of endophytic fungal extracts isolated from the roots of S. caseolaris. Morphological and molecular techniques were employed for fungal identification, while antibacterial activity was assessed using the disc diffusion assay, and antioxidant capacity was evaluated through the DPPH radical scavenging assay. The selected fungal isolate, RSC2, exhibited strong antibacterial and antioxidant activities. Thin Layer Chromatography (TLC) analysis confirmed the presence of flavonoid compounds, and molecular identification verified the isolate as Aspergillus niger. This study reports, for the first time, the isolation of A. niger from S. caseolaris roots with the ability to produce flavonoid metabolites exhibiting notable bioactive potential. These findings provide a scientific basis for future in vivo investigations aimed at developing natural compounds from mangrove-associated endophytes as promising pharmaceutical candidates.